Legal Protection for Village Heads in Exercising Government Authority: Analysis of Administrative Limits and Criminal Responsibility - Harmono Harmono (Politeknik Siber Cerdika Internasional, 2026)
Background: The expansion of administrative authority within the decentralization framework has increased the exposure to legal risks for village heads in Indonesia, particularly in the management of village finances. On one hand, village heads are required to exercise discretion to respond to community needs quickly and effectively; on the other hand, the administrative decisions they make often become targets of criminal law enforcement. This condition raises concerns about the phenomenon of criminalization of public policy at the village level. Objective: This study aims to analyze the construction of legal protection for village heads, identify the factors that cause criminalization, and formulate the boundary between administrative errors and criminal liability. Methods: This research employs a normative juridical method with statutory, conceptual, and case approaches, supported by current national and international literature. Results: The findings indicate that the existing legal protection framework remains fragmentary and lacks adequate doctrinal coherence, thereby creating legal uncertainty. The criminalization of village heads is influenced by regulatory disharmony, the dominance of repressive approaches in law enforcement, limited capacity of village officials, and local political dynamics. Furthermore, the absence of a clear boundary between administrative errors and criminal acts has led to the expansion of criminal law into the realm of government administration. Conclusion: This study offers a reconstruction of legal protection based on administrative law principles, particularly the principles of good faith, proportionality, and abuse of authority. It emphasizes that administrative review mechanisms must serve as a mandatory filter before the application of criminal law, so that the principle of ultimum remedium can be upheld. This research contributes to the global discourse on governance and legal accountability by offering a framework to prevent overcriminalization without compromising public sector integrity.